PENERAPAN KNOWLEDGE MANAGEMENT SYSTEM (Studi Kasus: Spesialis Penyakit Jantung dan Spesialis Penyakit Dalam di RSUD ABDUL MOELOEK) - Sasya Nadira; Rini Nurlistiani; Hendra Kurniawan; Agus Rahardi; Halimah Halimah (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2019)
Knowledge management is a concept that converts information into knowledge that can be followed up and available with easy means so that everyone can access it. The knowledge of information technology is very important for the community, as one of the software and forums providing information about stom and heart disease, which is located in Dr. H. Abdul Moeloek. In order to develop and maintain the process of learning, innovation and renewal must continue to develop and be sustainable and required facilities or activities that are able to provide information about health, website knowledge management system that is specific to heart and heart disease is designed using the waterfall model method. This website is built using the PHP programming language and MySQL as the database. This research resulted in a knowledge management system website. The use of this website can help the public in obtaining information, provide a forum for discussion and exchange of experiences regarding ulcer disease and heart disease.